Knowledge, Beliefs and Factors Affecting the Use of Generic Medicines among Patients in Ibb, Yemen: A Mixed-method Study - Al-Worafi, Yaser Mohammed; Alseragi, Wafa Mohammed; Alakhali, Khaled Mohamed; Ming, Long Chiau; Othman, Gamil; M Halboup, Abdulsalam; M. Alshahrani, Sultan; Alshakhshir, Sami Mustafa; Al-Shami, Abdulkareem Mohammed; Ali, Majid; Adam, Mansour; Wajid, Syed; et al. (Journal of Pharmacy Practice and Community Medicine)
Objectives: This study was aimed to explore the knowledge and beliefs of patients in Ibb, Yemen, regarding generic medicines and identify factors affecting their use of these medicines. Methods: A mixed qualitative and quantitative study was conducted between Jan 1 and Mar 31, 2017 in Ibb, Yemen. A total of 310 patients participated in this study. The questionnaire used for data collection comprised of two sections. The first section covered participants' demographic information and contained six questions addressing patients' ability to differentiate between generic and brand-name medications. The second section comprises 15 items regarding patients' beliefs about generic medicines, answered using a five-point Likert scale. Additionally, seven patients were interviewed using a semi-structured interview guide to explore further the factors affecting their generic medicine use. Results: Only 17.4% of patients knew the difference between generic and brand-name medicines. Approximately 59 (19%) patients believed that generic medicines' efficacy was the same as that of brand-name medicines, while 42 (13.5%) believed that generic medicines took longer to take effect. The vast majority of patients (252) (81.3%) believed that generic medicines were appropriate for less serious medical conditions. Only 84 patients (27.1%) believed that generic medications were the same as brand-name ones. Furthermore, the majority of patients held negative beliefs about generic medicines. The study also found that the price of medicines, physicians' recommendations, and pharmacy dispensers contributed to patients' use of generic medications. Conclusion: This study found that Yemen patients have insufficient knowledge of and negative beliefs about generic medicines. Special oriented and well-designed programs to educate and improve patients and healthcare professionals' understanding and beliefs about generic medicines are urgently needed.
Keywords: Generic medicine; Knowledge; Beliefs; Brand-name medicine; Yemen